FUNGSI DAN PERAN TINDAK TUTUR IMPERATIF TIDAK LANGSUNG DALAM BAHASA JEPANG - Yulia, Nova (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2015)
By using the indirect imperative speech acts, someone can give an order to other people without making the other person feel that he/she is being ordered or demeaned. However, sometimes the other person does not understand the meaning or message conveyed by the speaker. It can be based on the intention to keep the feeling of the partner in speaking in order not to feel like being ordered. Japanese language has a lot of forms of indirect speech imperative which are expressed pragmatically. This paper presents various forms of indirect speech imperative in Japanese language and when the utterance is used. Besides, this paper also discuss the variation of the imperative form of indirect speech act.Â Key words: speech act, imperative, sociolinguistics.